Full-Spectrum Analysis of Perovskite-Based Surface Plasmon Nanolasers - Pi-Ju Cheng; Qi-Yan Zheng; Chu-Yuan Hsu; Heng Li; Kuo-Bin Hong; Yizhi Zhu; Qiannan Cui; Chunxiang Xu; Tien-Chang Lu; Tzy-Rong Lin (Nanoscale Research Letters, 2020)
Abstract We systematically studied the characteristics of hybrid perovskite-based surface plasmon nanolasers. If one changes the anion composition of perovskites, the emission wavelength can be easily tuned. We conducted in full-spectrum modeling that featured hybrid perovskite nanowires placed on different SiO2-coated metallic (Au, Ag, and Al) plates. The proposed nanocavities that supported plasmonic gap modes exhibited distinguished properties of nanolasers, such as low-transparency threshold-gain and low lasing threshold. The corresponding experimental results for the MAPbBr3 nanolaser on Ag revealed the low-threshold operation. These superior features were attributed to enhanced light-matter interaction with strong coupling. Therefore, the proposed scheme, integrated with hybrid perovskite as gain material, provides an excellent platform for nanoscale plasmon lasing in the visible to near-infrared spectra.